2020
DOI: 10.1088/1757-899x/745/1/012072
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Thermal Radiation Heat Transfers in Agricultural Greenhouse

Abstract: The effects caused by convection and radiation heat transfer on the distribution of temperature, airflow and heat transfer in a greenhouse containing a heated solid block are studied numerically. Differential governing equations of the system are analyzed by utilized the finite volume method and the coupling of pressure-velocity is handled by the algorithm of SIMPLER. The systems algebraic equations are resolved by the conjugated of the gradient method. The greenhouse is supposed of an aspect ratio of A = 1.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…They were used the decision tree (DT) and multilayer perceptron (MLP) algorithms to create predictive models for hc, and their results showed that the DT algorithm was more successful in estimating hc values in greenhouse for forced convection drying (HDFC), while the MLP algorithm was more successful in estimating hc values in greenhouse for naturel convection drying (GDNC). Jehhef et al 12 investigated convective and radiative heat transfer effects on temperature, airflow, and heat exchange in a solid block‐heated greenhouse. Results emphasized the Rayleigh number's significant impact on flow and thermal structure.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…They were used the decision tree (DT) and multilayer perceptron (MLP) algorithms to create predictive models for hc, and their results showed that the DT algorithm was more successful in estimating hc values in greenhouse for forced convection drying (HDFC), while the MLP algorithm was more successful in estimating hc values in greenhouse for naturel convection drying (GDNC). Jehhef et al 12 investigated convective and radiative heat transfer effects on temperature, airflow, and heat exchange in a solid block‐heated greenhouse. Results emphasized the Rayleigh number's significant impact on flow and thermal structure.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, studying airflow and convective heat transfer in agricultural greenhouses is crucial for maintaining optimum growing conditions and minimizing production losses 3–21 . Factors influencing these processes include plant layout, outside temperature, wall and cover surfaces, convection mode, temperature, humidity, and ventilation 4–17 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations